Faculty Education, Academic Rank, and International Exposure as Drivers of University Internationalization: Evidence from an Indonesian Public University - Elin Rosalina; Iwan Sukoco; Herwan Abdul Muhyi (Business and Applied Management Journal, 2026)
Internationalization has become a strategic priority for universities, but evidence on how faculty-level human resource characteristics translate into measurable internationalization performance remains limited in developing-country universities. This study examines whether doctoral qualifications, professorial rank, professional teaching certification, and overseas educational background explain faculty-level internationalization performance at university. Using balanced panel data from 16 faculties over 2018-2024, the study constructs an internationalization performance index from active international collaborations, international students, and internationally indexed publications using principal component analysis. Panel regression is then estimated, with faculty budget included as a control variable and model selection based on Chow and Hausman tests. The results show that overseas educational background and faculty budget have positive and statistically significant effects on internationalization performance. Doctoral faculty shows a positive relationship in the baseline model, while the proportion of professors is negatively associated with internationalization performance and certified lecturers are not statistically significant. These findings suggest that formal academic status alone is insufficient to strengthen global engagement. Universities need internationally connected faculty development, incentives for global collaboration, and adequate faculty-level financial support to improve internationalization outcomes.